Decomposition of asbestos materials using fluoride wastes. Issue 1 (November 2021) - Necasova, K; Buchta, P; Chromkova, I; Stanek, T; Simbera, T
Abstract: Asbestos is one of the materials causing ecological stress. Due to its health harmfulness, an effective, ecological, and economic decomposition is highly desirable. One of the decomposition possibilities is a chemical decomposition, which could compete with commonly used thermal decomposition. The chemical decomposition can be accomplished both with the use of pure chemicals and waste chemicals from production technologies. This work deals with the use of technological wastes containing hydrofluoric acid or fluorides. Fluorides release hydrofluoric acid in the acid medium, which acts as the main decomposition medium. The source of fluorides was waste from the glass and metallic material industry. The efficiency of degradation processes was studied by mass analysis. Materials and decomposition products were characterized by X-ray powder diffraction.